2013
DOI: 10.1371/journal.pone.0063696
|View full text |Cite
|
Sign up to set email alerts
|

Group Behavioural Responses of Atlantic Salmon (Salmo salar L.) to Light, Infrasound and Sound Stimuli

Abstract: Understanding species-specific flight behaviours is essential in developing methods of guiding fish spatially, and requires knowledge on how groups of fish respond to aversive stimuli. By harnessing their natural behaviours, the use of physical manipulation or other potentially harmful procedures can be minimised. We examined the reactions of sea-caged groups of 50 salmon (1331±364 g) to short-term exposure to visual or acoustic stimuli. In light experiments, fish were exposed to one of three intensities of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…For example, studies in fisheries have already shown species attraction by shorter wavelength lights [4]. In parallel with fisheries, related studies have already shown promising results for salmon manipulation [17] and pathogen avoidance [5] through guidance in different swimming depths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, studies in fisheries have already shown species attraction by shorter wavelength lights [4]. In parallel with fisheries, related studies have already shown promising results for salmon manipulation [17] and pathogen avoidance [5] through guidance in different swimming depths.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, biorhythms have been related to feeding time, either in nature or aquaculture as well as under restricted feeding conditions [3]. In recent years, artificial light has been introduced in both fisheries [4] and aquaculture [5] towards attraction to specific areas and population guide for manipulation and avoidance of unfavorable conditions [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the use of environmental stimuli to alter fish distribution within cages has proven very successful , Bui et al 2013). Underwater lighting is commonly used to delay maturation in salmon aquaculture.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Salmon in sea cages alter their distribution and behaviour in response to numerous stimuli, including light ), temperature, salinity, feeding (Oppedal et al 2011a), water current velocity (Johansson et al 2014), sound (Bui et al 2013) and sea lice infestation level (Bui et al 2016). Given the myriad factors affecting salmon in sea cages, experimental testing within the marine cage environment is required to understand the behavioural trade-offs made by salmon in response to hypoxia and other environmental factors.…”
Section: Introductionmentioning
confidence: 99%